Fatty Acyl-CoA Reductase 1 Deficiency - Swisher, Charles N. (Pediatr Neurol Briefs, 2015)
Investigators from Erlangen, Germany; Calgary, CA; and Kafranbel, Syria, identified mutations in the gene, fatty acyl-CoA reductase 1 (FAR1) deficiency, adding to three other genes involved in plasmalogen biosynthesis, in two families affected by severe intellectual disability, early-onset epilepsy, microcephaly, congenital cataracts, growth retardation, and spasticity.